Psychophysiological and performance-related responses of a potentiation activity in swimmers of different competitive levels - Dalamitros, A. A.; Mavridis, G.; Semaltianou, E.; Loupos, D.; Manou, V. (Physiology & Behavior, 2019)
Highlights